The Use of Large Animal Models in Trauma and Bleeding Studies - Rayatdoost, Farahnaz; Grottke, Oliver (Hämostaseologie, 2023)
Background Major trauma often results in significant bleeding and coagulopathy, posing a substantial clinical burden. To understand the underlying pathophysiology and to refine clinical strategies to overcome coagulopathy, preclinical large animal models are often used. This review scrutinizes the clinical relevance of large animal models in hemostasis research, emphasizing challenges in translating findings into clinical therapies.Methods We conducted a thorough search of PubMed and EMBASE databases from January 1, 2010, to December 31, 2022. We used specific keywords and inclusion/exclusion criteria centered on large animal models.Results Our review analyzed 84 pertinent articles, including four animal species: pigs, sheep, dogs, and nonhuman primates (NHPs). Eighty-five percent of the studies predominantly utilized porcine models. Meanwhile, sheep and dogs were less represented, making up only 2.5% of the total studies. Models with NHP were 10%. The most frequently used trauma models involved a combination of liver injury and femur fractures (eight studies), arterial hemorrhage (seven studies), and a combination of hemodilution and liver injury (seven studies). A wide array of coagulation parameters were employed to assess the efficacy of interventions in hemostasis and bleeding control.Conclusions Recognizing the diverse strengths and weaknesses of large animal models is critical for trauma and hemorrhage research. Each model is unique and should be chosen based on how well it aligns with the specific scientific objectives of the study. By strategically considering each model's advantages and limitations, we can enhance our understanding of trauma and hemorrhage pathophysiology and further advance the development of effective treatments.
Keywords: trauma; hemorrhage; coagulation; hemostasis; animal models